INTEGRASI NILAI-NILAI PENDIDIKAN ISLAM DALAM TRADISI NAUNG RI ERE DI DESA BONTO SALAMA, SINJAI BARAT - Syaifin, Riyo Asmin; Wahyuni Annur; Ekawati; Akramuddin (Atta'dib Jurnal Pendidikan Agama Islam, 2025)
This study aims to examine the integration of Islamic educational values in the Naung Ri Ere tradition. The type of research used is qualitative research. The data collection techniques used include interviews, observation, and documentation. Data analysis techniques include data collection, data reduction, data presentation, and conclusion drawing. The findings show that the Naung Ri Ere tradition is a customary ritual performed in the context of marriage. The process begins with the preparation of halasuji, which is decorated with young coconut leaves and filled with offerings. The halasuji is then placed on the riverbank while prayers are recited by a sanro (traditional healer or ritual leader). After that, the halasuji is released into the river along with a chicken as part of the ritual. Community members then compete to retrieve the contents of the halasuji that are floating on the water. The newlyweds are baptised with river water as a symbol of purification. This tradition ends with a prayer of blessing at the couple's home, together with their family and the sanro. The Naung Ri Ere tradition reflects the integration of Islamic educational values through faith, morals, and sharia law, which complement each other. From a faith perspective, it strengthens faith by fostering gratitude to Allah SWT, although it needs to be corrected from beliefs that could potentially contradict tawhid. in terms of morals, this tradition is a means of social education that strengthens friendship, mutual cooperation, and maintains harmony in the household and community; while in terms of sharia, it demonstrates a dialogue between custom and religion, where cultural elements that are in line with Islam can be maintained and those that are contradictory can be abandoned, thus creating harmony between Bugis local wisdom and Islamic values.